THE EFFECT OF FIRE PROTECTION FACILITIES AND DISASTER RESPONSE SIMULATIONS ON INCREASING SKILLS IN FIRE FIGHTING AT POLTEKKES KEMENKES GORONTALO - Suwarni Loleh; Sukmawati Ahmad Damiti; Sulastri Pua Age (Universitas Negeri Gorontalo, 2022)
Data obtained from the National Disaster Management Agency (BNPB) in early 2014 to 2016 states that there are still many cases of fires occurring in Indonesia. Most people do not know the causes that often cause fires and the initial steps that must be taken when a fire occurs to minimize the losses caused. Practicing and building preparedness is necessary to deal with any emergency situation that is difficult to predict. Therefore, it is necessary to conduct a disaster emergency response simulation to find out the extent of knowledge and skills in fire disaster management, especially in the work area of the Health Poltekkes, Ministry of Health, Gorontalo. The research design used is a Quasy Experiment One Group Study (Pretest-Posttest) by measuring the independent variables (independent) consisting of fire emergency response simulations, while the dependent variable is fire disaster management knowledge and skills. The number of patient samples was calculated based on the Slovin formula obtained by 36 respondents using Univariate and Bivariate analysis methods through computer statistical programs. The time of the research will be carried out in June 2019. The results show that the fire prevention facilities in the Gorontalo Health Ministry Health Poltekkes work area are adequate but are constrained by the ability of electric power, but the knowledge and skills of employees within the Gorontalo District Health Office are adequate. Poltekkes based on statistical tests using paired sample T test obtained p = 0.000 (Î± = 0.05) which means that the fire emergency response simulation has an effect on increasing the knowledge and skills of employees in the Health Polytechnic of the Ministry of Health of Gorontalo in dealing with fire disasters.